The evaluation of the Zero In Consortium of museums - Ayala Museum, Lopez Museum, Ateneo Art Gallery, Museo Pambata and Bahay Tsinoy - Dionela, Jerik-James E.; Buenrostro, Iyra S. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
The main purpose of this study is to evaluate the Zero In consortium, which is composed of the following partner museums: (1) Ayala Museum; (2) Lopez Museum; (3) Ateneo Art Gallery; (4) Museo Pambata, and; (5) Bahay Tsinoy. The consortium was evaluated based on the following: (1) extent of the adherence of the consortium's programs and events to its principles; (2) if the consortium conforms to the proposed networking elements (resource sharing, bibliographic control, marketing strategies, and records management); (3) the extent of the members' contribution to the consortium (development and progress of the consortium since their inclusion to the group, operations and events of the consortium, marketing and promotion of the consortium, development and progress of the partner museums of the consortium), and; (4) the extent of the consortium's contribution to the partner museums.
Results have shown that the partner museums of Zero In are willing to share their resources; although they lack a formal agreement that would detail how their resources will be shared. The consortium markets itself well through the marketing efforts done by the partner museums. This, however, is inconclusive as the perception of the users was not taken into account. The libraries of the partner museums are not included in the resource sharing of the consortium; thus, the consortium does not have a bibliographic control nor a union catalog that lists down all the collection of their libraries. The consortium itself does not manage its own records. It is dependent on the records produced and managed by the partner museums. The partner museums contribute to the consortium in terms of: (1) its development and progress; (2) operations and events; (3) marketing and promotion, and; (4) development and progress of other partner museums. Also, the partner museums help the consortium in achieving its goals and vice versa.
Lastly, results indicate that the events and operations of the consortium are carried out in-line with its principles. Recommendations were given to serve as framework and to improve the Zero In consortium.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Zero In Consortium; Museums -- Philippines -- Manila Metropolitan Area; Museum cooperation -- Philippines -- Manila Metropolitan Area -- Evaluation